Analisis Perilaku Kerja Karyawan Pada PT. Indolakto Pasuruan - Yasman Yasman; Limgiani Limgiani (Jurnal Manajemen Kreatif dan Inovasi, 2024)
Employee work behavior can include their actions, attitudes, and opinions about their own work. All business organizations must understand the work behavior of their employees. Employee work behavior will influence company performance and direct the achievement of company goals. employee work behavior at PT. Indolakto Pasuruan is the subject of this research. Primary data was obtained through surveys, observations and interviews. This research involved all production department employees at PT. Indolakto Pasuruan, numbering 160 people. The results show that employees have motivation, can show work productivity, are responsible and work hard.